Neutralising linguistic sexism: Promising but cumbersome?. (August 2018) - Gabriel, Ute; Gygax, Pascal M.; Kuhn, Elisabeth A.
The generic use of grammatically (or lexically) gender-marked nouns and pronouns (GM) to refer to women and men in Indo-European languages has been criticised as gender-asymmetric since the 1970s. Two main strategies for eliminating asymmetry have been suggested: visibility by feminisation and de-gendering by neutralisation. Feminisation strategies seek to contribute to women's visibility in discourse by explicitly and symmetrically referring to women and men, thus continuing to highlight gender boundaries. In contrast, neutralisation strategies downplay gender boundaries by promoting the use of unmarked nouns and pronouns. We discuss feminisation and neutralisation strategies and review: (a) evidence (from our own work and that of others) on the effect of neutralisation and feminisation strategies on speakers' and readers' mental representations of gender and associated behaviours, and (b) evidence on individual variables facilitating and hampering the successful implementation of a less asymmetric—and therefore more gender-fair—language use. Based on this review, we suggest, in particular, to use feminisation strategies in contexts that are already gendered, and to use neutralisation strategies in nongendered ones (hence keeping the context gender-neutral).